Early “Celtic” identities in the Northern Italy and High Adriatic Authors - Linda Papi (Kosova Anthropologica)
This research aims to investigate the Celtic presence in Northern Italy and the High Adriatic during the phase prior to the historical invasion of 390 BC. According to the classical sources, at the beginning of the 4th century BC, Celtic communities crossed the Alps and settled in Italy. For ancient writers, this incursion was considered to be a brutal event, but archaeological evidence shows a different situation, suggesting that the Celtic presence in Italy can be traced back to the previous centuries. In the 5th century BC, Northern Italy was organized into large cultural entities which show close relations with the communities north of the Alps, based on the long-distance exchange system. In this diversified context, we observe the progressive diffusion of Late Hallstatt and La Tène elements. We will focus on the example of Adriatic Veneti earrings, found on both sides of the Adriatic Sea. Metal artifacts are an optimal field to reflect on this type of investigation. Their presence shows us the amplitude of individual mobility and allows us to deepen our knowledge about the strategies of cultural transfer, of the transmission of models, and of the circulation of people and goods.